When eastern India oscillated between desert versus savannah‐dominated vegetation - Zorzi, Coralie (2022)
During the last glacial period, the tropical hydrological cycle exhibited large variability across orbital and millennial timescales. However, the response of the Indian summer monsoon (ISM), its related impact on terrestrial ecosystems, and associated forcing mechanisms remain controversial. Here we present a marine record of pollen-inferred vegetation changes suggesting that eastern India shifted from woody-savanna mosaics during Marine Isotopic Stage 3 to grasslands during the Last Glacial Maximum resulting from large-scale drying. Our data shows that ISM maximum is in phase with obliquity and precession maxima suggesting a dominant role of the Indian Ocean interhemispheric temperature gradient on glacial ISM variability. Persistent and abrupt dryland expansions of varying magnitude suggest rapid-scale onset of aridity during Heinrich Stadial events and during the Toba eruption. We propose that the amplitude of ISM drought events are initiated by high latitude and volcanic forcings, although modulated by precession.